2009
DOI: 10.3390/md7040605
|View full text |Cite
|
Sign up to set email alerts
|

Marine Benthic Diatoms Contain Compounds Able to Induce Leukemia Cell Death and Modulate Blood Platelet Activity

Abstract: In spite of the high abundance and species diversity of diatoms, only a few bioactive compounds from them have been described. The present study reveals a high number of mammalian cell death inducing substances in biofilm-associated diatoms sampled from the intertidal zone. Extracts from the genera Melosira, Amphora, Phaeodactylum and Nitzschia were all found to induce leukemia cell death, with either classical apoptotic or autophagic features. Several extracts also contained inhibitors of thrombin-induced blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(35 citation statements)
references
References 35 publications
0
35
0
Order By: Relevance
“…Highly branched C25 isoprenoidpolyenes (polyunsaturated sesterpenes oils orhaslenes) were identified as being responsible for these activities [122]. A recent report documented that marine benthic diatoms contain compounds able to induce leukemia cell death and modulate blood platelet activity [123] suggesting that diatoms may represent a richer source of interesting bioactive compounds than previously recognized.…”
Section: Antipathogenic or Medical Applications Of Extracted Diatom Cmentioning
confidence: 92%
“…Highly branched C25 isoprenoidpolyenes (polyunsaturated sesterpenes oils orhaslenes) were identified as being responsible for these activities [122]. A recent report documented that marine benthic diatoms contain compounds able to induce leukemia cell death and modulate blood platelet activity [123] suggesting that diatoms may represent a richer source of interesting bioactive compounds than previously recognized.…”
Section: Antipathogenic or Medical Applications Of Extracted Diatom Cmentioning
confidence: 92%
“…Besides, it was also found that M. veneriformis contained nucleosides. Studies showed that nucleosides and their bases involved in regulating and modulating physiological processes in body and exhibited various bioactivities (Carver & Walker, 1995;Sánchez-Pozo & Gil, 2002), such as antiplatelet aggregation (Prestegard et al, 2009), antiarrhythmic (Headrick, Peart, Reichelt, & Haseler, 2011), anticancer (Prestegard et al, 2009;Shelton, Burt, & Peterson, 2011), and antioxidant (Tarozzi et al, 2010). For the long history of use, it is indeed necessary for establishing a proper method on the quality control of M. veneriformis both in food and TCM applications.…”
Section: Introductionmentioning
confidence: 98%
“…4. Cytotoxicity against acute myelogenic leukaemia cells has also recently been recently reported in extracts isolated from Norwegian benthic diatoms (Prestegard et al 2009). …”
Section: Anticancer Compounds Isolated From Diatomsmentioning
confidence: 97%